2016
DOI: 10.14446/fi.2016.239
|View full text |Cite
|
Sign up to set email alerts
|

New data on the macroflora of the basal Rotliegend group (Remigiusberg Formation; Gzhelian) in the Saar-Nahe basin (SW-Germany)

Abstract: New discoveries of fossil plant macroremains from the Remigiusberg Formation (lowermost Rotliegend group) considerably enlarge our knowledge about the flora of the basal-most part of the lithostratigraphically defined Rotliegend group within the Saar-Nahe Basin in SW-Germany. Most taxa are plants that grew in relatively humid habitats near rivers, or around margins of the lake in whose sediments the plant macroremains were found. This, together with previously reported palynological data, suggests that the wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Charbonnier, 2014). Other similar plant assemblages supporting a Stephanian C age for Coll de Sas floras are those from the Saar-Nahe basin of Germany (Kerp and Fichter, 1985;Uhl and Jasper, 2016), the Czech Republic basins (Opluštil et al, 2013(Opluštil et al, , 2017a(Opluštil et al, , 2017b, as well as from the further western Pangean equatorial basins (e.g., New…”
Section: Paleomagnetism: Magnetic Polarity Stratigraphymentioning
confidence: 92%
“…Charbonnier, 2014). Other similar plant assemblages supporting a Stephanian C age for Coll de Sas floras are those from the Saar-Nahe basin of Germany (Kerp and Fichter, 1985;Uhl and Jasper, 2016), the Czech Republic basins (Opluštil et al, 2013(Opluštil et al, , 2017a(Opluštil et al, , 2017b, as well as from the further western Pangean equatorial basins (e.g., New…”
Section: Paleomagnetism: Magnetic Polarity Stratigraphymentioning
confidence: 92%
“…Taxa from seasonally dry habitats occur throughout, including a diversity of callipterids and conifers. At the level of major group composition, these floras are quite similar to both Kola Switch and Sanzenbacher, but with a notable lack of Sphenopteris germanica; this latter species has since been reported from the lowermost Rotliegend (Uhl and Jasper 2016). In a quantitative study of two Lower and two Upper Rotliegend floras, Uhl and Lausberg (2008), who used the same methods of quantification as in the Kola Switch and Sanzenbacher studies, found conifers of various kinds to dominate three of the floras and callipterids to dominate the fourth.…”
Section: Comparison With Other Florasmentioning
confidence: 69%
“…Further comparison can be made to Rotliegend floras of Europe. The basic composition of such floras is summed up in the work of Barthel (2009) in addition to several summaries of more site-specific studies (e.g., Barthel 1976Barthel , 2016Lausberg and Kerp 2000;Šimůnek and Martínek 2009;Barthel et al 2010;Uhl and Jasper 2016). In the following, we focus on only two further summary papers, those of Kerp and Fichter (1985) and Uhl and Lausberg (2008), which examine broader ecological aspects of Lower and Upper Rotliegend floras in the Saar-Nahe Basin.…”
Section: Comparison With Other Florasmentioning
confidence: 99%